Efektivitas Penggunaan Media Jam Sudut pada Pembelajaran Matematika terhadap Motivasi Belajar Siswa SD - Sari, Nofa Permata; Al-Fath, Ayatullah Muhhamadin; Purnamasari, Mega Isvandiana (Scholarly Journal of Elementary School, 2021)
This research aims to: 1) Describe and know the use of Corner Clock learning media in high school Mathematics subjects at SDN Mentoro, 2) Describe and know the students' motivation in learning mathematics at SDN Mentoro, 3) Describe the use of Corner Clock media towards mathematics learning motivation of SDN Mentoro students. This research is qualitative research. The subject of this research was grade IV students at SDN Mentoro consisting of 13 male and 15 female students. Data collection techniques used were observation, interview questionnaire, and documentation. Data analysis techniques used the Miles and Huberman model consisting of data collection, data reduction, data presentation, and verification. The results of this research were: 1) The absence of Coner Clack media usage on mathematics learning in grade IV SDN Mentoro. 2) Thre result of questionnaires showed that there were two categories of students, namely high and low categories. It can be said that the motivation of learning grade IV students at SDN Mentoro was balanced between the two, 3) The two categories are approximately 91,3% stated in the category of excellent and 8,7% in the moderate category. Thus, it can be concluded that the students' motivation in learning mathematics by using the medium of Corner Clock showed better result and effective to use.